Reflexiones en torno a la logística de aprovisionamiento: antecedentes y tendencias - Parra Peña, Javier; Niño Villamizar, Yeny Andrea; Suárez Serrano, Mónica Yinette (Ingeniería, 2022)
Context: Procurement is each time more important from the strategic point of view of the organizations. It has generated several tendencies in its management. The academic reflection about its evolution, from a traditional focus, which unique criteria of decision making is the cost, to achieve a level of strategic cooperation, invites to have an integral looked of this function in the supply chain context. Method: From the review of academic documents, we acquired relevant information and classified it in the issues antecedents, current state, and tendencies of the procurement function. These issues orientate the authors' reflections. Results: As two of the results of the reflection are the process transformation and the improvement of relationships with providers, achieving long term alliances needs; digitalization and its influence in the manner in which transactions occur; the validity of the purchasing analysis in maturity models; the integration present in the co-maker ship and the challenges related with sustainability and value recovering. Conclusions: Because of the strategic importance of procurement function to get competitive levels proposed by organizations, from the academic ambit, it should be a reflection and research permanent, especially about digitalization, dynamic supply chain, and sustainability. In this context, this document orientates the analysis related to advances in procurement function and present several of the future research topics in it.